The future of labour market reform in the Gulf region towards a multi-disciplinary, evidence-based and practical understanding - Jones, David B.; Sahraoui, Sofiane (Gulf Research Center book series, 2018)
As governments across the GCC strive to implement labour policies which accelerate the transition to "post oil" knowledge-based economies, this volume provides insights into the size of this challenge, along with analysis of progress to date. With a comprehensive coverage of the region (each GCC member is included in some respect), this new work provides unique insights into how the domestic policy agenda is shifting the region's moribund labour markets inexorably towards greater productivity, positivity, sustainability and efficiency. This volume is based on a workshop held at the Gulf Research Meeting organized by the Gulf Research Center Cambridge in summer 2016.